Is endoscopy mandatory in cases mimicking acute pancreatitis? - Mohammed Hussien Ahmed; Mohammed Said Radwan; Amira Amin Salem Tawoos3; Rasha Ibrahim Salama (Journal of the Pakistan Medical Association, 2023)
N/A